Emotional Impact of End-of-Life Decisions on Professional Relationships in the ICU: An Obstacle to Collegiality?*. Issue 12 (December 2017) - Laurent, Alexandra; Bonnet, Magalie; Capellier, Gilles; Aslanian, Pierre; Hebert, Paul
Abstract : Objectives: End-of-life decisions are not only common in the ICU but also frequently elicit strong feelings among health professionals. Even though we seek to develop more collegial interprofessional approaches to care and health decision-making, there are many barriers to successfully managing complex decisions. The aim of this study is to better understand how emotions influence the end-of-life decision-making process among professionals working in ICU. Design: Qualitative study with clinical interviews. All interviews were transcribed verbatim and analyzed thematically using interpretative phenomenological analysis. Setting: Two independent ICUs at the "Centre Hospitalier de l'Université de Montréal." Subjects: Ten physicians and 10 nurses. Interventions: None. Measurements and Main Results: During the end-of-life decision-making process, families and patients restructure the decision-making frame by introducing a strong emotional dimension. This results in the emergence of new challenges quite different from the immediacy often associated with intensive care. In response to changes in decision frames, physicians rely on their relationship with the patient's family to assist with advanced care decisions. Nurses, however, draw on their relationship and proximity to the patient to denounce therapeutic obstinacy. Conclusions: Our study suggests that during the end-of-life decision-making process, nurses' feelings toward their patients and physicians' feelings toward their patients' families influence the decisions they make. Although these emotional dimensions allow nurses and physicians to act in a manner that is consistent with their professional ethics, the professionals themselves seem to have a poor understanding of these dimensions and often overlook them, thus hindering collegial decisions. Abstract : Supplemental Digital Content is available in the text.